Software for adapting the material balance model of a gas field development object using the Monte Carlo method - V. Zarubin, Yu. Zarubin (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2023)
The publication is a logical continuation of works on the creation of convenient software for operational analysis and forecasting of indicators of a separate gas field development object based on the material balance model. The main requirements for such a software object were accessibility, low costs for hardware and software, ease of use for a researcher without special computer and mathematical knowledge, a minimum of input data, which in turn protects against unreliable, and sometimes unavailable model parameters. The software, with a minimum of information and labor costs, allows to identify the mode of operation of the deposit, estimate the initial gas reserves, determine the activity of the water-bearing zone, give a forecast of gas and condensate production according to the modes of operation of the wells.